Correlates of recovery for Canadian Atlantic cod ( Gadus morhua) 1 This review is part of the virtual symposium “Flagship Species – Flagship Problems” that deals with ecology, biodiversity and management issues, and climate impacts on species at risk and of Canadian importance, including the polar bear ( Ursus maritimus), Atlantic cod ( Gadus morhua), Piping Plover ( Charadrius melodus), and caribou ( Rangifer tarandus). - Hutchings, Jeffrey A.; Rangeley, Robert W. (Canadian Journal of Zoology, 2011)
The collapse of Atlantic cod ( Gadus morhua L., 1758) in the early 1990s, perhaps the greatest numerical loss of a Canadian vertebrate (1.5–2.5 billion reproductive individuals), is one from which the species has yet to recover. Populations, or stocks, are at or well below their conservation reference points. The lack of recovery has been linked to ongoing fishing mortality (targeted, bycatch), changes to life history (reductions in age and size at maturity, truncations in age and size structure), and increased natural mortality. Emergent and demographic Allee effects, coupled with altered interspecific interactions, render questionable the presumption that the recovery of heavily depleted populations can be reliably forecasted by population dynamical behaviour during decline. Contrary to international commitments and inconsistent with fishery rebuilding plans elsewhere, cod recovery plans exclude target and limit reference points, recovery timelines, and harvest control rules. We suggest that the long-term biodiversity, social, and economic benefits associated with cod recovery can be realised by novel changes, including quantitatively responsible recovery plans based on science-determined reference points, new or revised legislation, integrated management strategies, strengthened sustainable seafood certification practices, expansion of marine spatial planning and protected areas, and novel financial incentives for investment in long-term, sustainable fisheries.